Urban road planning: a safety perspective - Sara Ferreira (2011)
The planning process is the first stage to incorporate the safety analysis of the road urban network. This paper provides a tool that allows the analysis of the potential accident risk at urban segments using information available at road planning process. The main points decided in the planning stage - land-use and the road function classification - were used as explanatory variables. Other variables, as control variables, were included such as traffic flow, segment length, minor intersections density and time trend. Generalized linear modeling techniques were used to model accident data from Porto, Portugal. The models outcomes demonstrated that all the variables are statistically significant and according to the expectation. Using the "percentage explained" by the model it can be concluded that although the traffic flow was the strongest variable, the land-use and road function classification have improved the "percentage explained" by the model. Â(c) 2011 ASCE.